Collective passenger transportation: An outsourcing case in Integra S.A. (2020)
This article documents the experience of the company INTEGRA SA and its outsourcing process of tire maintenance and vehicle washing, the impact of this process is reflected on the operational costs by the flexibility in its procedure, the speed achieved in services and time savings, which are translated into profitability; in addition, it gives the possibility of focusing the operation on key processes.